Plasticity of muscle synergies through fractionation and merging during development and training of human runners - Cheung, Vincent C. K.; Cheung, Ben M. F.; Zhang, Janet H.; Chan, Zoe Y. S.; Ha, Sophia C. W.; Chen, Chao-Ying; Cheung, Roy T. H. (Nature communications, 2020)
Complex motor commands for human locomotion are generated through the combination of motor modules representable as muscle synergies. Recent data have argued that muscle synergies are inborn or determined early in life, but development of the neuro-musculoskeletal system and acquisition of new skills may demand fine-tuning or reshaping of the early synergies. We seek to understand how locomotor synergies change during development and training by studying the synergies for running in preschoolers and diverse adults from sedentary subjects to elite marathoners, totaling 63 subjects assessed over 100 sessions. During development, synergies are fractionated into units with fewer muscles. As adults train to run, specific synergies coalesce to become merged synergies. Presences of specific synergy-merging patterns correlate with enhanced or reduced running efficiency. Fractionation and merging of muscle synergies may be a mechanism for modifying early motor modules (Nature) to accommodate the changing limb biomechanics and influences from sensorimotor training (Nurture). Motor commands for human locomotion are generated by combination of muscle synergies. In humans, muscle synergies for running exhibit considerable plasticity during child-to-adult development and adult training to meet the constantly changing biomechanical and efficiency demands.